The European Union's Nuclear Non-proliferation Policy - Herrera, Manuel (Taylor & Francis, 2025)
This book looks at European Union (EU) attempts to manage the risks associated with nuclear non-proliferation and assesses its performance and external challenges. The introductory section delves into current academic scholarship, elucidating the concepts of contestation and performance. The second section provides an overview of the historical and institutional evolution, and the third scrutinizes the performance. The final section examines present policy, with case studies on the EU's bilateral relations with Iran and India. Adopting a focus on both the development and performance of the EU’s non-proliferation and disarmament policy, as well as its contestation from non-Western countries, this book provides a solid and innovative contribution to existing debates on both the EU’s non-proliferation and foreign policy. The book will appeal to scholars, researchers and practitioners of International Relations, European Union Studies and Nuclear Non-Proliferation, as it provides an analysis of the intricacy of the EU’s non-proliferation policy, offering fresh perspectives and empirical evidence.